การศึกษาเอกลักษณ์จังหวัดอุดรธานี เพื่อออกแบบรถสามล้อระบบไฮบริด, The Study of Udon Thani Province’s Identity for Hybrid Tricycle Design - เรืองวรรณศักดิ์ กนิษฐา (Asian Creative Architecture, Art and Design, 2018)
Abstract The study of the motor tricycle structure and identity of Udon Thani province aims to take off for the motor tricycle hybrid system design which could be able communicate to the identity of Udon Thani Province and to evaluate satisfaction from the tourists towards the motor tricycle hybrid system accomplishment. The samples selection were 300 native respondents which are purposive sampling. The tools used in this research were the questionnaires to gather design guidelines from people in Udon Thani and the satisfaction evaluation form towards the product prototype by tourists. The results revealed the optimal identity have conducted to the motor tricycle design that was the identity from Ban Chiang world heritage especially Lai Kod Kon Hoi pattern or spiral pattern due to Ban Chiang have well known as the world heritage for Thai people and foreigners. The hen tags has been a specific area obviously and the most important tourist attraction of Udon Thani province. The color tone and pattern of design must be in harmony or related to Udon Thani province color which was the orange color for more distinct. Furthermore, the structure development must be consideration about the safety imporfrntly, easy for producing and repairing. The guideline design before production were the follows. Firstly the hybrid system consists of the system driven by solar energy with installed solar panel on the top of canvas roof of motor tricycle and electrical energy by using the 4 batteries. The batteries were stored on the pick-up of passengers zone through the driver zone. The battery compretmout was provided to support a heavy weight of batteries. The passengers area zone for walking and seating is the same. Secondl production was inspired by mixing of Lai Kod Kon Hoi pattern, arranging the pottery form at the left-right structure obviously decorated with S-pattern. The material was stainless steel durable for the weather. A main color was orange as the Bastard Teak flower color which is the color of Udon Thani province. The cushion of seat was decorated with red color instead of Ban Chiang painted design. The evaluation prototype result found that the satisfaction of motor tricycle design with hybrid system was at a high level. The design identity characteristic obviously communicate a the characteristic of Udon Thani province. Keywords: Motor Tricycle, Udon Thani Province Identity, Hybrid System